Consequences of immigrating during a recession: Evidence from the US Refugee Resettlement program - Joshua Mask (IZA Journal of Development and Migration, 2020)
Are there long-term labor consequences in migrating to the US during a recession? For most immigrants, credibly estimating this effect is difficult because of selective migration. Some immigrants may not move if economic conditions are not favorable. However, identification is possible for refugees as their arrival dates are exogenously determined through the US Refugee Resettlement program. A one percentage point increase in the arrival national unemployment rate reduces refugee wages by 1.98% and employment probability by 1.57 percentage points after 5 years.
Keywords: J15; J24; J31; J41; J61; 330; immigration; labor market outcomes; settlement policies; recession